Boon of MTA Apexification in Young Permanent Posterior Teeth - Vinod Kumar; Mohammed Zameer; Vijaya Prasad; T. Mahantesh (Case Reports in Dentistry)
Single visit apexification using mineral trioxide aggregate (MTA) is a new boon in effective management of nonvital tooth with an open apex which has steadily gained popularity with clinicians; also it shortens the treatment period and improves patient compliance. Importance of this approach lies in expedient cleaning and shaping of the root canal system, followed by its apical seal with MTA. There are several case reports available describing the use of MTA as an apexification agent in incisors and premolar, but presented cases are the unique case reports demonstrating successful apexification procedure using MTA in young permanent mandibular molars. After eight-month follow-up, teeth were without any abnormal clinical symptoms; rather there were radiographic resolution of the periapical lesion and induction of root end closure with new hard tissue formation over MTA.